Exploring the culture of excellence in a clinical trial unit: an ethnographic reflection / Shubashini Gnanasan - Gnanasan, Shubashini (Faculty of Pharmacy, 2025)
Ethnography is a powerful yet underutilized research methodology that involves immersive, long-term observation to understand cultural and organisational dynamics. During my year-long fellowship at the Oxford Centre for Clinical Magnetic Resonance Research, Radcliffe Department of Medicine, University of Oxford, I had the privilege of experiencing this firsthand. This opportunity honed my skills as a researcher, challenged my comfort zone, and fostered resilience.